SISTEM PEMANTAUAN PERTUMBUHAN BATITA MENGGUNAKAN METODE FUZZY TSUKAMOTO - Irma Anggraeni; Yusma Yanti (KOMPUTASI, 2020)
The growth of children under the age of three (toddlers) is one of the determinants of children's development in the future. One of the parameters of toddler growth assessment is determined by gender, age, height and weight. This research makes a system that can monitor toddler growth with web-based. The research method used is the System Life Development Cycle, which consists of planning, analysis, design, implementation and use. This system also uses the Tsukamoto fuzzy method to determine the membership set of each input variable. The gender criteria are divided into two classes, male and female, the age criteria are divided into three classes, the height criteria are three classes, and the weight criteria are divided into three classes. Based on the division of classes, the output of this study is the growth status of toddlers, namely poor growth, poor, normal and more. Based on the results of input data criteria and calculations using Tsukamoto fuzzy, the output obtained in the form of the status of the child's growth.